Kikir dalam Al-Qur’an (Kajian Lafadz Al-Bukhl dan Asy-Syuhh Menurut Tafsîr Fii Zhilalil Qur’an) - Addini, Nur Futiha; Iqbal, Ipmawan Muhammad; Ridho, Muhammad Mukharom (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This study examines the meaning and consequences of the Qur'an with a focus on the analysis of the Faazaz al-Bukhl and Asy-Syuhh in the interpretation of the Quran by Sayyid Quthb. The Quran is one of the most famous interpretations for its thematic and in-depth approach to the Quran, providing valuable insight into this topic. The results of the research show that al-Bukhl and asy-Syuhh are perverse properties that are rooted in liver disease and have a negative impact on individual and social lives. The Quran reveals the profound meaning of both of these affairs, linking them with the concepts of tauhid, zakat, and infak, and emphasizing the importance of avoiding the nature of kikir as an effort for the salvation of the world and the Hereafter.